A pressure and shear sensor system for stress measurement at lower limb residuum/socket interface. Issue 7 (July 2016) - Laszczak, P.; McGrath, M.; Tang, J.; Gao, J.; Jiang, L.; Bader, D.L.; Moser, D.; Zahedi, S.
Highlights: A sensor system is reported to measure pressure and shear in lower limb prosthetics. Static and dynamic performance was calibrated using mechanical test machine. Pilot amputee test was conducted to measure stresses at residuum/socket interface. Amputee test results and analysis preliminarily validate sensor system performance. Abstract: A sensor system for measurement of pressure and shear at the lower limb residuum/socket interface is described. The system comprises of a flexible sensor unit and a data acquisition unit with wireless data transmission capability. Static and dynamic performance of the sensor system was characterised using a mechanical test machine. The static calibration results suggest that the developed sensor system presents high linearity (linearity error ≤ 3.8%) and resolution (0.9 kPa for pressure and 0.2 kPa for shear). Dynamic characterisation of the sensor system shows hysteresis error of approximately 15% for pressure and 8% for shear. Subsequently, a pilot amputee walking test was conducted. Three sensors were placed at the residuum/socket interface of a knee disarticulation amputee and simultaneous measurements were obtained during pilot amputee walking test. The pressure and shear peak values as well as their temporal profiles are presented and discussed. In particular, peak pressure and shear of approximately 58 kPa and 27 kPa, respectively, were recorded. Their temporal profiles also provide dynamic coupling information at this critical residuum/socket interface. These preliminary amputee test results suggest strong potential of the developed sensor system for exploitation as an assistive technology to facilitate socket design, socket fit and effective monitoring of lower limb residuum health.